2004
DOI: 10.1158/1078-0432.ccr-03-0424
|View full text |Cite
|
Sign up to set email alerts
|

Trastuzumab (Herceptin) Enhances Class I-Restricted Antigen Presentation Recognized by HER-2/neu-Specific T Cytotoxic Lymphocytes

Abstract: Purpose: Numerous examples from animal models and clinical trials showed that HER-2-derived peptides are naturally processed as a CTL epitope and can be recognized by tumor-specific CTLs in several tumors with HER-2 overexpression. The humanized anti-HER-2 monoclonal antibody, Herceptin, has been designed to specifically antagonize the HER-2 function by directing against the extracellular domain of the HER-2 protein. One of the actions of Herceptin includes the internalization and degradation of HER-2, which m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 28 publications
3
46
0
Order By: Relevance
“…In fact, we and others reported that clinical vaccination trials in gastric or breast cancer patients using DCs pulsed with HER-2 peptides confirmed the fact that vaccination with HER-2 peptides is immunogenic, and that HER-2 could be a good target for immunotherapy (Disis et al, 1999;Kono et al, 2002c). Furthermore, we have recently shown that Herceptin enhances MHC class Irestricted antigen presentation in HER-2-overexpressing tumours, resulting in a higher susceptibility of HER-2-overexpressing tumours to lysis by HER-2-specific CTL (Kono et al, 2004). These results suggested that the combination of Herceptin and anti-HER-2-specific CTLs may result in a synergic antitumour effect in oesophageal SCC.…”
Section: Discussionmentioning
confidence: 88%
“…In fact, we and others reported that clinical vaccination trials in gastric or breast cancer patients using DCs pulsed with HER-2 peptides confirmed the fact that vaccination with HER-2 peptides is immunogenic, and that HER-2 could be a good target for immunotherapy (Disis et al, 1999;Kono et al, 2002c). Furthermore, we have recently shown that Herceptin enhances MHC class Irestricted antigen presentation in HER-2-overexpressing tumours, resulting in a higher susceptibility of HER-2-overexpressing tumours to lysis by HER-2-specific CTL (Kono et al, 2004). These results suggested that the combination of Herceptin and anti-HER-2-specific CTLs may result in a synergic antitumour effect in oesophageal SCC.…”
Section: Discussionmentioning
confidence: 88%
“…Interestingly, trastuzumab has been shown to enhance the cytotoxicity of ErbB-2-specific cytotoxic T lymphocytes (CTLs). Through enhanced endocytic degradation of ErbB-2, trastuzumab was shown to enhance MHC class I presentation of ErbB-2 epitopes, resulting in a higher susceptibility of ErbB-2 tumors to lysis by CTLs (30,31). Taken together, these data suggest that the combined administration of anti-DR5 mAb and trastuzumab may synergize in the generation of antitumor adaptive immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…The Her2/neu receptor is considered a good target for Ab-mediated immunotherapeutic approaches because it is expressed at high levels in many tumors but at low levels in normal cells (28). Within the Her2/neu protein there are multiple HLA-A2 binding peptide epitopes that can induce CTL responses against autologous tumor cells (15,29).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, drugtreated cells showed a 2-fold increase in HLA-A2 surface expression and a 15% increase in 1B8 staining (data not shown), suggesting that factors such as chaperones may provide protection from the proteasomal degradation pathway and that dissociation of these complexes may lead to enhanced lysis by CTLs. Other studies have shown that the internalization of Her2/neu mediated by trastuzumab can enhance tumor cell sensitivity to CTL-mediated lysis, and it is hypothesized that this is due to an increase in Her2/ neu peptide-HLA-A2 complexes on the cell surface (28). This theory can now be tested directly using the 1B8 TCRm to assess the presentation of the dominant Her2 (369) -A2 epitope.…”
Section: Discussionmentioning
confidence: 99%